Elementary school teachers' perception of Dengue and its environmentally friendly prevention: A focus group study - Lilik Zuhriyah; Dearikha Karina Mayashinta; Nia Kurnianingsih; Holipah Holipah; Aulia Rahmi Pawestri (AOSIS, 2019)
Understanding teachers' perceptions towards dengue prevention in schools is an important factor for an optimal implementation of dengue prevention and control measures. This qualitative study aimed to explore teachers' perceptions of dengue and its prevention in an environmentally friendly manner. 31 informants were chosen from 6 elementary schools. Data were obtained by Focus Group Discussion (FGD) and then analyzed by using Systematic Text Condensation and an editing analysis style. The results showed that the teachers confirmed the presence of patients with dengue hemorrhagic fever from students and residents living around the school. Most teachers agree and want to know about ovitrap applications in school, which is environmentally friendly. However, most teachers refuse to manage inorganic waste because of the bad experience. Engaging teachers in dengue prevention in schools has a high potential for success as long as it is efficient in terms of time and effort.